Learning Planning Strategies To Improve Student Achievement - Widodo (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang OKU Timur Sumatera Selatan, 2025)
Learning Planning Strategies to Improve Student Achievement is a crucial aspect in efforts to enhance student performance. Effective learning planning strategies must be tailored to the needs of students as well as the conditions of the learning environment to support the improvement of learning outcomes. This study aims to explore various learning planning strategies that contribute to increasing student achievement. Learning planning strategies consist of a series of activities that organize the use of methods, media, administration, and learning resources in an integrated manner to achieve predetermined learning objectives. The results of this study are expected to provide deep insights into how to optimize learning planning to significantly support students' academic success.